High-thermal-conductivity filler and magnetized graphene oxide hybridized phase change microcapsule and preparation method thereof

By introducing high thermal conductivity fillers and magnetized graphene oxide in phase change microcapsules, the problems of insufficient thermal conductivity and volume expansion and leakage after microencapsulation are solved, and the phase change with high thermal conductivity and stability are achieved Microcapsules, suitable for thermal management of electronic devices.

CN119391383APending Publication Date: 2025-02-07CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411581275.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing phase change materials have insufficient thermal conductivity in the thermal management of electronic equipment, and the problems of volume expansion and leakage after microencapsulation limit their application.

Method used

Using highly thermally conductive filler and magnetic graphene oxide hybrid phase transition microcapsules, paraffin as core material and inorganic compounds as shell material, a stable core-shell structure is formed, and nano-copper oxide and multi-walled are added to the microcapsules. High thermal conductivity fillers such as carbon nanotubes improve thermal conductivity.

Benefits of technology

The thermal conductivity, morphological stability and heat storage/release rate of phase-change microcapsules are significantly improved, and are suitable for heat transfer fields within the temperature range of 40 to 100°C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391383A_ABST
    Figure CN119391383A_ABST
Patent Text Reader

Abstract

The invention provides a high-thermal-conductivity filler and magnetized graphene oxide hybridized phase change microcapsule and a preparation method thereof, and relates to the technical field of phase change materials, the phase change microcapsule is of a core-shell structure, a paraffin material is adopted as a core material, an inorganic compound material is adopted as a shell material, the ratio of the core material to the shell material is 2: 1, and the particle size of the core material to the shell material is 2: 1. The high-thermal-conductivity filler comprises one or more of nano copper oxide, multi-walled carbon nanotubes, nano boron nitride, nano boron carbide, expanded graphite and the like. Meanwhile, the invention also provides a preparation method of the phase change microcapsule. The preparation method has the advantages that the morphological stability and the leakage-proof performance of the modified phase change microcapsule are improved. And a uniform and clear magnetized graphene oxide interface layer is formed between the melamine-formaldehyde resin shell and the paraffin core, so that the heat transfer rate among particles is enhanced. The modified paraffin melamine-formaldehyde resin microcapsule has relatively high thermal conductivity, morphological stability and excellent heat storage and release rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of phase change materials, and in particular relates to phase change microcapsules hybridized with high thermal conductivity fillers and magnetized graphene oxide, and a preparation method thereof. Background Art

[0002] In the thermal management of electronic devices, the heat generated by electronic circuits must be removed to avoid premature failure and improve long-term sustainability. Heat sinks based on thermal energy storage have been widely used in electronic packaging as a passive thermal management option.

[0003] Phase change materials have desirable properties such as high latent heat, inertness, low price, and bulk availability. Paraffin wax is more suitable and adaptable to practical applications due to its thermal stability and durability. However, volume expansion and leakage during the solid-liquid phase change process limit the performance of paraffin wax. Microencapsulation is one of the best methods currently available, which encapsulates the core phase change material in a shell material, thereby limiting the leakage and reactivity of the phase change material with the external environment.

[0004] Furthermore, due to the low thermal conductivity of microencapsulated phase change materials, the heat transfer performance of organic phase change materials such as paraffin is limited. Adding thermally conductive fillers to phase change materials can promote uniform heat transfer and melting, thereby improving their heat transfer capacity. For example, nano-additives such as metal fins, porous materials, and carbon materials such as flake graphite play a significant role in the thermal transfer performance of materials, whether in the core phase change material or the shell. For these reasons, the present invention provides a phase change microcapsule hybridizing a highly thermally conductive filler and magnetized graphene oxide, and a method for preparing the same. Summary of the Invention

[0005] In view of the above problems in the prior art, the present invention is proposed.

[0006] Therefore, the present invention provides a phase-change microcapsule hybridized with a high thermal conductivity filler and magnetized graphene oxide and a preparation method thereof.

[0007] To solve the above technical problems, the present invention provides the following technical solution: the phase change microcapsule has a stable core-shell structure, wherein the core material is paraffin, the shell material is an inorganic compound, and the ratio of the core material to the shell material is 2:1.

[0008] As a preferred embodiment of the preparation method of the hybrid phase-change microcapsules of high thermal conductivity filler and magnetized graphene oxide described in the present invention, the high thermal conductivity filler includes one or more of nano-copper oxide, multi-walled carbon nanotubes, nano-boron nitride, nano-boron carbide, expanded graphite, nano-silicon carbide, nano-magnesium oxide or nano-zinc oxide.

[0009] As a preferred solution of the method for preparing the hybrid phase-change microcapsules of high thermal conductivity filler and magnetized graphene oxide described in the present invention, it is characterized in that the water content of the core material paraffin is less than 3%.

[0010] As a preferred embodiment of the method for preparing the hybrid phase-change microcapsules of high thermal conductivity filler and magnetized graphene oxide described in the present invention, it is characterized in that the inorganic compound is one or more of melamine-formaldehyde, silicon dioxide, titanium dioxide or calcium carbonate.

[0011] A preferred embodiment of the method for preparing the hybrid phase-change microcapsules of high thermal conductivity filler and magnetized graphene oxide according to the present invention is characterized in that it specifically comprises the following steps:

[0012] (1) Preparation of graphene oxide

[0013] Graphene flakes are oxidized using potassium permanganate in the presence of sulfuric acid and phosphoric acid. After being stored at room temperature for a period of time, the mixture is filtered and washed with distilled water to obtain magnetized graphene oxide blocks, which are then vacuum dried at room temperature.

[0014] (2) Preparation of magnetized graphene oxide

[0015] Using nickel chloride hexahydrate and sodium hydroxide as catalysts, graphene oxide was sonicated in 100 ml of ethylene glycol, and then the reaction mixture was stored at 80 °C for 2 h, washed with deionized water and centrifuged.

[0016] (3) Preparation of high thermal conductivity filler:

[0017] Magnetic graphene oxide, a highly thermally conductive filler, was dispersed in deionized water using continuous ultrasound to prepare magnetic graphene oxide suspensions of varying concentrations. The ultrasound temperature was maintained at room temperature until the filler particles were uniformly dissolved in the aqueous phase to form an aqueous dispersion.

[0018] (4) Preparation of emulsion:

[0019] 100ml of deionized water, 5g of paraffin wax, 1.5g of sodium dodecyl sulfate, and 0.5g of sodium hydroxide were placed in a three-necked round-bottom flask. Then, nano-boron carbide, nano-copper oxide, and magnetic graphene oxide (a highly thermally conductive filler) dispersed in deionized water at varying concentrations were added to the reaction mixture in the three-necked flask. The pH of the system was adjusted to acidic, and the mixture was stirred at 600 rpm for 30 minutes at 70°C.

[0020] (5) Preparation of melamine-formaldehyde prepolymer solution:

[0021] 2.5 g of melamine and 7.5 ml of formaldehyde were mixed with deionized water to form a melamine-formaldehyde prepolymer solution under a magnetic stirrer at 70° C. until the milky white solution became clear and transparent.

[0022] (6) Preparation of high thermal conductive fillers / phase change microcapsules:

[0023] Melamine-formaldehyde prepolymer was added dropwise to the solution in a flask at a constant rate, with continuous stirring to form a stable emulsion. The reaction was then terminated by adjusting the pH with ethylenediamine. After the reaction, the mixture was cooled to room temperature, washed several times with deionized water at 70°C to neutralize and remove unreacted paraffin, and then dried under vacuum. Modified paraffin / melamine-formaldehyde microcapsules (with a highly thermally conductive filler) and unmodified paraffin / melamine-formaldehyde microcapsules (without a thermally conductive filler) were prepared.

[0024] As a preferred embodiment of the method for preparing the hybrid phase-change microcapsules of high thermal conductivity filler and magnetized graphene oxide according to the present invention, it is characterized in that in the step (1), the mass ratio of potassium permanganate to graphene is 3:1.

[0025] As a preferred embodiment of the method for preparing the hybrid phase-change microcapsules of high thermal conductivity filler and magnetized graphene oxide described in the present invention, it is characterized in that, in the step (1), the volume ratio of sulfuric acid to phosphoric acid is 9:1.

[0026] As a preferred embodiment of the method for preparing the hybrid phase-change microcapsules of high thermal conductivity filler and magnetized graphene oxide described in the present invention, it is characterized in that, in the step (1), the oxidation time is 24 to 72 hours.

[0027] As a preferred embodiment of the method for preparing the hybrid phase-change microcapsules of high thermal conductivity filler and magnetized graphene oxide described in the present invention, it is characterized in that, in the step (2), the mass ratio of the graphene oxide to nickel chloride hexahydrate is 1:2.

[0028] As a preferred embodiment of the method for preparing the hybrid phase-change microcapsules of high thermal conductivity filler and magnetized graphene oxide according to the present invention, it is characterized in that, in the step (2), the number of centrifugation is 6 to 12 times.

[0029] As a preferred embodiment of the method for preparing the hybrid phase-change microcapsules of high thermal conductivity filler and magnetized graphene oxide according to the present invention, it is characterized in that, in the step (6), the dripping rate is 3 ml / min.

[0030] As a preferred embodiment of the method for preparing the hybrid phase-change microcapsules of high thermal conductivity filler and magnetized graphene oxide according to the present invention, it is characterized in that in the step (6), the stirring rate is 400 to 1000 rpm.

[0031] As a preferred embodiment of the method for preparing the hybrid phase-change microcapsules of high thermal conductivity filler and magnetized graphene oxide described in the present invention, it is characterized in that, in the step (6), the stirring time is 2 to 5 hours.

[0032] As a preferred embodiment of the method for preparing the hybrid phase-change microcapsules of high thermal conductivity filler and magnetized graphene oxide according to the present invention, it is characterized in that in the step (6), the pH is adjusted to 8-9.

[0033] Beneficial effects of the present invention:

[0034] Phase-change microcapsules modified with high-thermal-conductivity fillers such as nano-boron carbide, nano-copper oxide, and magnetized graphene oxide exhibit enhanced morphological stability and leak-proof properties. A uniform and distinct magnetized graphene oxide interface layer forms between the melamine-formaldehyde resin shell and the paraffin wax core, enhancing interparticle heat transfer. Consequently, the paraffin-based melamine-formaldehyde resin microcapsules modified with magnetized graphene oxide exhibit high thermal conductivity, morphological stability, and excellent heat storage / release rates. They can be used in heat transfer applications within a temperature range of 40–100°C, demonstrating their potential in high-temperature heat transfer applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] To more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. Those skilled in the art can also derive other drawings based on these drawings without inventive effort. Among them:

[0036] Figure 1 This is a scanning electron microscope image of the modified phase change microcapsules prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0037] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0038] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0039] Secondly, the term "one embodiment" or "embodiment" herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in various places throughout this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive of other embodiments.

[0040] Unless otherwise specified, the raw materials used in the present invention are all commercially available.

[0041] Example 1

[0042] (1) Preparation of emulsion:

[0043] Place 100ml of deionized water, 5g of paraffin wax, 1.5g of sodium dodecyl sulfate, and 0.5g of sodium hydroxide in a three-necked round-bottom flask. Add 8mg of nano-copper oxide to the reaction mixture in the three-necked flask, adjust the pH to acidic, and stir at 70°C and 600 rpm for 30 minutes.

[0044] (2) Preparation of melamine-formaldehyde prepolymer solution:

[0045] 2.5 g of melamine and 7.5 ml of formaldehyde were mixed with deionized water to form a melamine-formaldehyde prepolymer solution under a magnetic stirrer at 70° C. until the milky white solution became clear and transparent.

[0046] (3) Preparation of high thermal conductive fillers / phase change microcapsules:

[0047] Melamine-formaldehyde prepolymer was added dropwise to the solution at a rate of 3 ml / min and stirred continuously at 600 rpm for 3 hours to form a stable emulsion. The reaction was then terminated by adjusting the pH to 8-9 with ethylenediamine. After the reaction, the mixture was cooled to room temperature, washed several times with deionized water at 70°C to neutralize and remove unreacted paraffin, and then vacuum dried. This resulted in the preparation of modified paraffin / melamine-formaldehyde microcapsules (with thermally conductive fillers).

[0048] Example 2

[0049] (1) Preparation of high thermal conductivity filler:

[0050] Magnetic graphene oxide, a highly thermally conductive filler, was dispersed in deionized water using continuous ultrasound to prepare magnetic graphene oxide suspensions of varying concentrations. The ultrasound temperature was maintained at room temperature until the filler particles were uniformly dissolved in the aqueous phase to form an aqueous dispersion.

[0051] (2) Preparation of emulsion:

[0052] Place 100ml of deionized water, 5g of paraffin wax, 1.5g of sodium dodecyl sulfate, and 0.5g of sodium hydroxide in a three-necked round-bottom flask. Then, add 5mg of nano-boron carbide and 8mg of nano-copper oxide to the reaction mixture in the three-necked flask. Adjust the pH to acidic and stir at 70°C and 600 rpm for 30 minutes.

[0053] (3) Preparation of melamine-formaldehyde prepolymer solution:

[0054] 2.5 g of melamine and 7.5 ml of formaldehyde were mixed with deionized water to form a melamine-formaldehyde prepolymer solution under a magnetic stirrer at 70° C. until the milky white solution became clear and transparent.

[0055] (4) Preparation of high thermal conductive fillers / phase change microcapsules:

[0056] Melamine-formaldehyde prepolymer was added dropwise to the solution at a rate of 3 ml / min and stirred continuously at 600 rpm for 3 hours to form a stable emulsion. The reaction was then terminated by adjusting the pH to 8-9 with ethylenediamine. After the reaction, the mixture was cooled to room temperature, washed several times with deionized water at 70°C to neutralize and remove unreacted paraffin, and then vacuum dried. This resulted in the preparation of modified paraffin / melamine-formaldehyde microcapsules (with thermally conductive fillers).

[0057] Example 3

[0058] The difference between this embodiment and embodiment 2 is that the mass of boron nitride is adjusted to 10 mg, and the rest of the preparation process is the same as that of embodiment 2 to obtain a modified paraffin wax / melamine-formaldehyde microcapsule sample powder.

[0059] Example 4

[0060] The difference between this embodiment and embodiment 2 is that the mass of boron nitride is adjusted to 15 mg, and the rest of the preparation process is the same as that of embodiment 2 to obtain a modified paraffin wax / melamine-formaldehyde microcapsule sample powder.

[0061] Example 5

[0062] The difference between this embodiment and embodiment 2 is that the mass of boron nitride is adjusted to 20 mg, and the rest of the preparation process is the same as that of embodiment 2 to obtain a modified paraffin wax / melamine-formaldehyde microcapsule sample powder.

[0063] Example 6

[0064] (1) Preparation of graphene oxide

[0065] 0.2 g of graphene flakes were oxidized with 0.6 g of potassium permanganate in the presence of 9 ml of sulfuric acid and 1 ml of phosphoric acid. After storage at room temperature for 72 h, the mixture was filtered and washed with distilled water to obtain magnetized graphene oxide blocks, which were then dried in vacuum at room temperature.

[0066] (2) Preparation of magnetized graphene oxide

[0067] Using 60 mg of nickel chloride hexahydrate and 0.5 g of sodium hydroxide as catalysts, 30 mg of graphene oxide was sonicated in 100 ml of ethylene glycol, and then the reaction mixture was stored at 80 °C for 2 h, washed with deionized water and centrifuged 6 times.

[0068] (3) Preparation of high thermal conductivity filler:

[0069] Magnetic graphene oxide, a highly thermally conductive filler, was dispersed in deionized water using continuous ultrasound to prepare magnetic graphene oxide suspensions of varying concentrations. The ultrasound temperature was maintained at room temperature until the filler particles were uniformly dissolved in the aqueous phase to form an aqueous dispersion.

[0070] (4) Preparation of emulsion:

[0071] Place 100ml of deionized water, 5g of paraffin wax, 1.5g of sodium dodecyl sulfate, and 0.5g of sodium hydroxide in a three-necked round-bottom flask. Then, add 8mg of nano-copper oxide and 0.5mg / ml of magnetic graphene oxide to the reaction mixture in the three-necked flask. Adjust the pH to acidic and stir at 600 rpm for 30 minutes at 70°C.

[0072] (5) Preparation of melamine-formaldehyde prepolymer solution:

[0073] 2.5 g of melamine and 7.5 ml of formaldehyde were mixed with deionized water to form a melamine-formaldehyde prepolymer solution under a magnetic stirrer at 70° C. until the milky white solution became clear and transparent.

[0074] (6) Preparation of high thermal conductive fillers / phase change microcapsules:

[0075] Melamine-formaldehyde prepolymer was added dropwise to the solution at a rate of 3 ml / min and stirred continuously at 600 rpm for 3 hours to form a stable emulsion. The reaction was then terminated by adjusting the pH to 8-9 with ethylenediamine. After the reaction, the mixture was cooled to room temperature, washed several times with deionized water at 70°C to neutralize and remove unreacted paraffin, and then vacuum dried. This resulted in the preparation of modified paraffin / melamine-formaldehyde microcapsules (with thermally conductive fillers).

[0076] Example 7

[0077] The difference between this embodiment and embodiment 6 is that the concentration of magnetic graphene oxide is adjusted to 1 mg / ml, and the rest of the preparation process is the same as that of embodiment 6 to obtain a modified paraffin wax / melamine-formaldehyde microcapsule sample powder.

[0078] Example 8

[0079] The difference between this embodiment and embodiment 6 is that the concentration of magnetic graphene oxide is adjusted to 1.5 mg / ml, and the rest of the preparation process is the same as that of embodiment 6 to obtain a modified paraffin wax / melamine-formaldehyde microcapsule sample powder.

[0080] Example 9

[0081] The difference between this embodiment and embodiment 6 is that the concentration of magnetic graphene oxide is adjusted to 2 mg / ml, and the rest of the preparation process is the same as that of embodiment 6 to obtain a modified paraffin wax / melamine-formaldehyde microcapsule sample powder.

[0082] Experimental Example 1

[0083] The thermal conductivity of the materials and paraffin wax prepared in Examples 1 to 9 was tested. The thermal conductivity coefficient of the paraffin wax / melamine-formaldehyde phase change microcapsules modified with thermal conductive fillers is shown in Table 1.

[0084] Table 1 Thermal conductivity test results

[0085] sample Thermal conductivity (W / mK) paraffin 0.23 Example 1 0.35 Example 2 0.36 Example 3 0.38 Example 4 0.37 Example 5 0.36 Example 6 0.38 Example 7 0.40 Example 8 0.38 Example 9 0.37

[0086] Analyzing the above table, we can draw the following conclusions:

[0087] (1) Comparing Example 1 with Examples 6 to 9, the thermal conductivity of the phase change microcapsules is the highest when the concentration of magnetic graphene oxide is 1 mg / ml, which is 0.4 W / mK. As the concentration of magnetic graphene oxide exceeds 1 mg / ml, the thermal conductivity of the phase change microcapsules shows a downward trend, which is due to the thin thickness of the shell material. As the concentration of high thermal conductive filler increases, the shells of some modified phase change microcapsules are destroyed by the thermal conductive filler, the core material leaks out, and small-sized cavities appear, so the thermal conductivity is low. In Examples 2 to 5, a similar situation occurs when the mass of nano-boron carbide is adjusted to exceed 10 mg. Therefore, on the basis of adding nano-copper oxide, the optimal addition amount of the best single high thermal conductive filler magnetic graphene oxide or nano-copper oxide should be 1 mg / ml or 10 mg.

[0088] (2) Comparing Example 3 and Example 7, the thermal conductivity of the phase change microcapsules modified with magnetic graphene oxide is greater. This is because magnetic graphene oxide is crucial to improving the thermal conductivity of the incorporated phase change microcapsules, because the graphene oxide network they form on the core phase change material improves the heat transfer inside the phase change microcapsules by enhancing the thermal diffusion coefficient.

[0089] (3) Based on nano-copper oxide, the thermal conductivity of phase change microcapsules prepared by adding any filler is much higher than that of paraffin wax itself. In addition, the effect of nano-boron carbide on the thermal conductivity of phase change microcapsules is weaker than that of changing the high thermal conductivity filler magnetic graphene oxide.

[0090] Example 10

[0091] (1) Preparation of graphene oxide

[0092] 0.2 g of graphene flakes were oxidized with 0.6 g of potassium permanganate in the presence of 9 ml of sulfuric acid and 1 ml of phosphoric acid. After storage at room temperature for 72 h, the mixture was filtered and washed with distilled water to obtain magnetized graphene oxide blocks, which were then dried in vacuum at room temperature.

[0093] (2) Preparation of magnetized graphene oxide

[0094] Using 60 mg of nickel chloride hexahydrate and 0.5 g of sodium hydroxide as catalysts, 30 mg of graphene oxide was sonicated in 100 ml of ethylene glycol, and then the reaction mixture was stored at 80 °C for 2 h, washed with deionized water and centrifuged 6 times.

[0095] (3) Preparation of high thermal conductivity filler:

[0096] Magnetic graphene oxide, a highly thermally conductive filler, was dispersed in deionized water using continuous ultrasound to prepare magnetic graphene oxide suspensions of varying concentrations. The ultrasound temperature was maintained at room temperature until the filler particles were uniformly dissolved in the aqueous phase to form an aqueous dispersion.

[0097] (4) Preparation of emulsion:

[0098] Place 100ml of deionized water, 5g of paraffin wax, 1.5g of sodium dodecyl sulfate, and 0.5g of sodium hydroxide in a three-necked round-bottom flask. Then, add 10mg of nano-boron carbide, 8mg of nano-copper oxide, and 0.5mg / ml of magnetic graphene oxide to the reaction mixture in the three-necked flask. Adjust the pH to acidic and stir at 70°C and 600 rpm for 30 minutes.

[0099] (5) Preparation of melamine-formaldehyde prepolymer solution:

[0100] 2.5 g of melamine and 7.5 ml of formaldehyde were mixed with deionized water to form a melamine-formaldehyde prepolymer solution under a magnetic stirrer at 70° C. until the milky white solution became clear and transparent.

[0101] (6) Preparation of high thermal conductive fillers / phase change microcapsules:

[0102] Melamine-formaldehyde prepolymer was added dropwise to the solution at a rate of 3 ml / min and stirred continuously at 600 rpm for 3 hours to form a stable emulsion. The reaction was then terminated by adjusting the pH to 8-9 with ethylenediamine. After the reaction, the mixture was cooled to room temperature, washed several times with deionized water at 70°C to neutralize and remove unreacted paraffin, and then vacuum dried. This resulted in the preparation of modified paraffin / melamine-formaldehyde microcapsules (with thermally conductive fillers).

[0103] Example 11

[0104] The difference between this embodiment and embodiment 10 is that the concentration of magnetic graphene oxide is adjusted to 1 mg / ml, and the rest of the preparation process is the same as that of embodiment 10, to obtain a modified paraffin wax / melamine-formaldehyde microcapsule sample powder.

[0105] Example 12

[0106] The difference between this embodiment and embodiment 10 is that the concentration of magnetic graphene oxide is adjusted to 1.5 mg / ml, and the rest of the preparation process is the same as that of embodiment 10, to obtain a modified paraffin wax / melamine-formaldehyde microcapsule sample powder.

[0107] Example 13

[0108] The difference between this embodiment and embodiment 10 is that the concentration of magnetic graphene oxide is adjusted to 2 mg / ml, and the rest of the preparation process is the same as that of embodiment 19, and the modified paraffin / melamine-formaldehyde microcapsule sample powder is obtained.

[0109] Example 14

[0110] (1) Preparation of graphene oxide

[0111] 0.2 g of graphene flakes were oxidized with 0.6 g of potassium permanganate in the presence of 9 ml of sulfuric acid and 1 ml of phosphoric acid. After storage at room temperature for 72 h, the mixture was filtered and washed with distilled water to obtain magnetized graphene oxide blocks, which were then dried in vacuum at room temperature.

[0112] (2) Preparation of magnetized graphene oxide

[0113] Using 60 mg of nickel chloride hexahydrate and 0.5 g of sodium hydroxide as catalysts, 30 mg of graphene oxide was sonicated in 100 ml of ethylene glycol, and then the reaction mixture was stored at 80 °C for 2 h, washed with deionized water and centrifuged 6 times.

[0114] (3) Preparation of high thermal conductivity filler:

[0115] Magnetic graphene oxide, a highly thermally conductive filler, was dispersed in deionized water using continuous ultrasound to prepare magnetic graphene oxide suspensions of varying concentrations. The ultrasound temperature was maintained at room temperature until the filler particles were uniformly dissolved in the aqueous phase to form an aqueous dispersion.

[0116] (4) Preparation of emulsion:

[0117] Place 100ml of deionized water, 5g of paraffin wax, 1.5g of sodium dodecyl sulfate, and 0.5g of sodium hydroxide in a three-necked round-bottom flask. Then, add 5mg of nano-boron carbide, 8mg of nano-copper oxide, and 1mg / ml of magnetic graphene oxide to the reaction mixture in the three-necked flask. Adjust the pH to acidic and stir at 600 rpm for 30 minutes at 70°C.

[0118] (5) Preparation of melamine-formaldehyde prepolymer solution:

[0119] 2.5 g of melamine and 7.5 ml of formaldehyde were mixed with deionized water to form a melamine-formaldehyde prepolymer solution under a magnetic stirrer at 70° C. until the milky white solution became clear and transparent.

[0120] (6) Preparation of high thermal conductive fillers / phase change microcapsules:

[0121] Melamine-formaldehyde prepolymer was added dropwise to the solution at a rate of 3 ml / min and stirred continuously at 600 rpm for 3 hours to form a stable emulsion. The reaction was then terminated by adjusting the pH to 8-9 with ethylenediamine. After the reaction, the mixture was cooled to room temperature, washed several times with deionized water at 70°C to neutralize and remove unreacted paraffin, and then vacuum dried. This resulted in the preparation of modified paraffin / melamine-formaldehyde microcapsules (with thermally conductive fillers).

[0122] Example 15

[0123] The difference between this embodiment and embodiment 14 is that the mass of boron carbide is adjusted to 15 mg, and the rest of the preparation process is the same as that of embodiment 14, to obtain a modified paraffin wax / melamine-formaldehyde microcapsule sample powder.

[0124] Example 16

[0125] The difference between this embodiment and embodiment 14 is that the mass of boron carbide is adjusted to 20 mg, and the rest of the preparation process is the same as that of embodiment 14, to obtain a modified paraffin wax / melamine-formaldehyde microcapsule sample powder.

[0126] Comparative Example 1

[0127] (1) Preparation of high thermal conductivity filler:

[0128] Expanded graphite, a high thermal conductivity filler, was dispersed in deionized water by continuous ultrasonication to prepare expanded graphite suspensions of varying concentrations. The ultrasonication temperature was maintained at room temperature until the filler particles were uniformly dissolved in the aqueous phase to form an aqueous dispersion.

[0129] (2) Preparation of emulsion:

[0130] Place 100ml of deionized water, 5g of paraffin wax, 1.5g of sodium dodecyl sulfate, and 0.5g of sodium hydroxide in a three-necked round-bottom flask. Then, add 10mg of nano-boron carbide, 8mg of nano-copper oxide, and 1mg / ml of expanded graphite to the reaction mixture in the three-necked flask. Adjust the pH to acidic and stir at 70°C and 600 rpm for 30 minutes.

[0131] (3) Preparation of melamine-formaldehyde prepolymer solution:

[0132] 2.5 g of melamine and 7.5 ml of formaldehyde were mixed with deionized water to form a melamine-formaldehyde prepolymer solution under a magnetic stirrer at 70° C. until the milky white solution became clear and transparent.

[0133] (4) Preparation of high thermal conductive fillers / phase change microcapsules:

[0134] Melamine-formaldehyde prepolymer was added dropwise to the solution at a rate of 3 ml / min and stirred continuously at 600 rpm for 3 hours to form a stable emulsion. The reaction was then terminated by adjusting the pH to 8-9 with ethylenediamine. After the reaction, the mixture was cooled to room temperature, washed several times with deionized water at 70°C to neutralize and remove unreacted paraffin, and then vacuum dried. This resulted in the preparation of modified paraffin / melamine-formaldehyde microcapsules (with thermally conductive fillers).

[0135] Experimental Example 2

[0136] The thermal conductivity of the materials prepared in the above examples and comparative examples was tested. The thermal conductivity coefficient results of the paraffin wax / melamine-formaldehyde phase change microcapsules without thermal conductive fillers and with thermal conductive fillers are shown in Table 1.

[0137] Table 1 Thermal conductivity test results

[0138]

[0139]

[0140] Analyzing the above table, we can draw the following conclusions:

[0141] (1) Comparing Example 3, Example 7, and Example 11, the thermal conductivity coefficients of these three are 0.38 W / mK, 0.4 W / mK, and 0.45 W / mK, respectively. It can be shown that the thermal conductivity coefficient of the modified phase change microcapsules when multiple high thermal conductivity fillers are added is higher than the thermal conductivity coefficient when a single high thermal conductivity filler is added. The thermal conductivity value of the phase change material significantly affects its ability to store thermal energy and the speed at which it transfers heat. It is crucial to select the appropriate high thermal conductivity filler and its dosage.

[0142] (2) Comparing Example 11 with Comparative Example 1, the thermal conductivity of the high thermal conductivity filler in the comparative example, 1 mg / ml magnetic graphene oxide, was changed to 1 mg / ml expanded graphite, which decreased to 0.43 W / mK. This is due to the cohesive interaction between the magnetized co-filler particles, which resulted in minimal unidirectional heat flow inside the phase-change microcapsules. Therefore, the magnetized thermally conductive filler can significantly improve the heat storage efficiency of the phase-change microcapsules. Compared with the thermal conductivity of paraffin wax itself, the thermal conductivity of the microcapsules modified with magnetized graphene oxide increased by two times, making them suitable for thermal energy storage and release applications.

[0143] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. Phase change microcapsules hybridized with high thermal conductive filler and magnetized graphene oxide, characterized in that: The phase-change microcapsule has a core-shell structure including a core material and a shell material, wherein the core material is made of paraffin material, the shell material is made of inorganic compound material, and the ratio of the core material to the shell material is 2:

1.

2. The phase-change microcapsule hybridized with a thermally conductive filler and magnetized graphene oxide according to claim 8, characterized in that: The high thermal conductivity filler includes one or more of nano copper oxide, multi-walled carbon nanotubes, nano boron nitride, nano boron carbide, expanded graphite, nano silicon carbide, nano magnesium oxide or nano zinc oxide.

3. The phase-change microcapsule hybridized with high thermal conductive filler and magnetized graphene oxide according to claim 1, characterized in that: The water content of the paraffin in the core material is less than 3%.

4. The phase-change microcapsule hybridized with high thermal conductive filler and magnetized graphene oxide as claimed in claim 3, characterized in that: The inorganic compound is one or more of melamine-formaldehyde, silicon dioxide, titanium dioxide or calcium carbonate.

5. The method for preparing the phase-change microcapsules hybridized with high thermal conductive filler and magnetized graphene oxide according to any one of claims 1 to 4, characterized in that: The specific steps include: S1: Preparation of graphene oxide, using potassium permanganate to oxidize graphene flakes in the presence of sulfuric acid and phosphoric acid, storing the mixture at room temperature for a period of time, filtering the mixture, washing it with distilled water, and obtaining magnetized graphene oxide blocks, which were then dried in vacuum at room temperature. S2: Preparation of magnetized graphene oxide, using nickel chloride hexahydrate and sodium hydroxide as catalysts, graphene oxide was sonicated in 100 ml of ethylene glycol, and then the reaction mixture was stored at 80 °C for 2 h, washed with deionized water and centrifuged; S3: Preparation of high thermal conductivity filler: dispersing high thermal conductivity filler magnetic graphene oxide into deionized water by continuous ultrasound to prepare magnetic graphene oxide suspensions of different concentrations. The temperature of the ultrasound is maintained at room temperature until the filler particles are uniformly dissolved in the water phase to form a water dispersion; S4: Preparation of emulsion: 100 ml of deionized water, 5 g of paraffin, 1.5 g of sodium dodecyl sulfate, and 0.5 g of sodium hydroxide were placed in a three-necked round-bottom flask in sequence. Then, nano-boron carbide, nano-copper oxide, and magnetic graphene oxide, a high thermal conductive filler dispersed in deionized water of different concentrations, were added to the reaction mixture in the three-necked flask, the pH of the system was adjusted to acidic, and stirred at 70°C at a speed of 600 rpm for 30 min; S5: Preparation of melamine-formaldehyde prepolymer solution: 2.5 g of melamine and 7.5 ml of formaldehyde were mixed with deionized water to form a melamine-formaldehyde prepolymer solution under a magnetic stirrer at 70° C. until the milky white solution became clear and transparent; S6: Preparation of high thermal conductive filler / phase change microcapsules: Melamine-formaldehyde prepolymer was added dropwise to a flask containing a solution at a certain rate and stirred continuously to form a stable emulsion. Then, the pH was adjusted with ethylenediamine to terminate the reaction. After the reaction was completed, it was cooled to room temperature, washed with deionized water at 70°C for multiple times, neutralized to remove unreacted paraffin, and then vacuum dried to prepare modified paraffin / melamine-formaldehyde microcapsules with high thermal conductive fillers and unmodified paraffin / melamine-formaldehyde microcapsules without thermal conductive fillers.

6. The method for preparing the phase-change microcapsules hybridized with high thermal conductive filler and magnetized graphene oxide according to claim 5, characterized in that: In the step S1, the mass ratio of potassium permanganate to graphene is 3:1, the volume ratio is 9:1, and the oxidation time is 24 to 72 hours.

7. The method for preparing the phase-change microcapsules hybridized with high thermal conductive filler and magnetized graphene oxide according to claim 5, characterized in that: In the step S2, the mass ratio of the graphene oxide to the nickel chloride hexahydrate is 1:2, and the number of centrifugation is 6 to 12 times.

8. The method for preparing the phase-change microcapsules hybridized with high thermal conductive filler and magnetized graphene oxide according to claim 5, characterized in that: In step S6, the dripping rate is 3 ml / min.

9. The method for preparing the phase-change microcapsules hybridized with high thermal conductive filler and magnetized graphene oxide according to claim 5, characterized in that: In the step S6, the stirring rate is 400-1000 rpm, the stirring time is 2-5 hours, and the pH value is adjusted to 8-9.